(Re)starting the tourism business during a crisis? Challenges and decisions to reopen of guest house entrepreneurs in the Maldives. Issue 7 (3rd April 2022) - Chia, Kei Wei; Anas, Ahmed
ABSTRACT: The purpose of the study is to investigate the challenges and response decisions of guesthouse entrepreneurs in reopening their business during a health crisis. Using a qualitative inquiry with 25 guesthouse entrepreneurs, the findings identify four challenges and four reasons to reopen their business. This study enhances the understanding of micro, small, and medium enterprises (MSME) entrepreneurial decision making under crisis conditions and its implications for the tourism and hospitality industry. This study also offers readers an understanding of the challenges and decisions of small accommodation entrepreneurs in re-launching their operations at this critical time and serves as a reminder to small businesses about the potential challenges in their business recovery operations and proposes feasible management strategies to refer to as a contingency of a probable future crisis.